NOUN PHRASE ANALYSIS OF MAGAZINE ARTICLE “VIDEO GAMES … ARE GOOD FOR YOU?” BY GABRIEL J. ADAMS - Egi Nurdiansyah; Intan Satriani (PROJECT (Professional Journal of English Education), 2021)
Understanding the text is one of the objectives of English study. Before understanding the complex sentence the basic skill that student need to master is to understand the phrases of each sentence. This article objectives are to give more understanding about noun phrases in magazine article to help student easy to understand the basic of English especially phrase. The reason writer choose noun phrase is the most commonly used phrase in the sentence is the noun phrase and the writer want to make the reader familiar with noun phrase. This article will analyze the magazine article with 22 sentences and also contains 66 noun phrases in it. Which the writer will determine the modifier every noun phrase in it. Therefore, mastering phrases is a key to become a fluent speaker of English. Keywords:  Noun Phrases, Magazine Article